2020
DOI: 10.3892/or.2020.7581
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the Wnt/β‑catenin signaling pathway on apoptosis in HeLa cells induced by carbon ion irradiation

Abstract: The molecular mechanisms underlying the biological effects of carbon ions are unclear. The aim of this study was to explore the Wnt/β-catenin pathway in regulating carbon ion ( 12 C 6+ ) radiation-induced cellular toxicity. HLY78 is a Wnt-specific small molecular modulator, whose effects on 12 C 6+ radiation-induced damage are mostly unknown. HLY78, in combination with 12 C 6+ radiation was investigated on HeLa cell viability, cell cycle progression, DNA damage, and the expression of apoptotic and Wnt-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Carbon ions were found to downregulate the expression of Wnt3a and β‐catenin in proliferating HeLa cells, consistent with our previous findings (Si et al, 2020; Zhang et al, 2020). In contrast, carbon ions upregulated Wnt3a and β‐catenin levels in quiescent cells, thereby activating the β‐catenin signaling pathway.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Carbon ions were found to downregulate the expression of Wnt3a and β‐catenin in proliferating HeLa cells, consistent with our previous findings (Si et al, 2020; Zhang et al, 2020). In contrast, carbon ions upregulated Wnt3a and β‐catenin levels in quiescent cells, thereby activating the β‐catenin signaling pathway.…”
Section: Discussionsupporting
confidence: 92%
“…The β‐catenin signaling pathway plays a substantial role in tumorigenesis and tumor propagation. Our previous studies revealed that inhibition of Wnt/β‐catenin signaling effectively sensitizes HeLa cells to carbon ion radiation, whereas activation of Wnt/β‐catenin signaling reduces carbon ion radiation‐induced dysfunction in human cervical cancer HeLa cells (Si et al, 2020; Zhang et al, 2020). These results verified that β‐catenin signaling is involved in the regulation of the radiosensitivity of HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HLY78 is an agonist of the Wnt/β-catenin signaling pathway. HLY78 can enhance Wnt signaling by targeting the DIX domain of Axin in the channel and enhancing Axin-LRP6 cross-linking [ 48 , 49 , 50 ]. We pretreated with the Wnt agonist HLY78 to investigate the crucial utility of ginsenoside Rh4.…”
Section: Discussionmentioning
confidence: 99%